ANALISIS PERKEMBANGAN PAJAK TRANSAKSI PERDAGANGAN MELALUI SISTEM ELEKTRONIK (PMSE) DI INDONESIA - Tofan, Ali; Trinaningsih, Sri (Balance : Jurnal Akuntansi dan Bisnis, 2022)
This research was conducted with the objectives to analyze the e-commerce tax in Indonesia in terms of the development of tax laws and regulations related to the e-commerce. The research method used is descriptive qualitative research, namely library research. The type of research literature conducted by the researcher is observation and documentation. The researcher selects things that are observed and recorded according to the purposes of the research, collects various information relating to the research that obtained from a variety of sources that previous research, internet pages, articles, and laws and regulations in the field of taxation and regulations of e-commerce, then drawn a conclusion based on the opinion of the researcher. The results showed that: 1. The e-commerce tax was initially treated the same through regulations SE-62/PJ/2013 which emphasized that e-commerce transactions were the same as conventional trade transactions and no new taxes were imposed. 2. Since 2020 the e-commerce tax in the form of e-commerce VAT released with the issuance of regulation regulations PMK 48/PMK.03/2020 and Per-12/PJ/2020.  E-commerce tax receipts based on the DGT's official website from September 2020 to August 2021 e-commerce VAT collections more than IDR 2.5 Trillion